A devil's bargain with transposable elements in plant pathogens. Issue 3 (March 2022) - Fouché, Simone; Oggenfuss, Ursula; Chanclud, Emilie; Croll, Daniel
Abstract : Transposable elements (TEs) spread in genomes through self-copying mechanisms and are a major cause of genome expansions. Plant pathogens have finely tuned the expression of virulence factors to rely on epigenetic control targeted at nearby TEs. Stress experienced during the plant infection process leads to derepression of TEs and concurrently allows the expression of virulence factors. We argue that the derepression of TEs elements causes an evolutionary conflict by favoring TEs that can be reactivated. Active TEs and recent genome size expansions indicate that plant pathogens could face long-term consequences from the short-term benefit of fine-tuning the infection process. Hence, encoding key virulence factors close to TEs under epigenetic control constitutes a devil's bargain for pathogens. Highlights: Many filamentous pathogens have compartmentalized genomes with gene-rich and gene-poor regions where genes involved in virulence (i.e., effectors) are often located near TEs. TEs govern the regulation of effector genes in TE-rich compartments through epigenetic effects. This enables tight regulatory timing with the plant infection but incurs long-term risks to host genome integrity. We refer to this as the devil's bargain of the plant pathogens. TE activation can have drastic fitness consequences for the host, such as the disruption of essential genes and mediating chromosome rearrangements. TE activation can drive genome size expansions over evolutionary time. The exact sequence of evolutionary events tying effector regulation and TEs remains poorly understood. Genomic surveys and epigenetic analyses have the potential to unravel causal mechanisms.